Sustainability assessment of waste cooking oil-based biodiesel plant in developing economy based on F-DEMATEL and F-ISM approaches - Jangre, Jogendra (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
Developing clean and renewable energy resources for long-term usage is a crucial concern in developing countries. In this regard, biodiesel technology is drawing a lot of public interest throughout the world. The issues associated with the sustainability of a biodiesel plant are intimately connected with restricted natural resources, political influences, energy independence, economic prosperity and global stability. Therefore, this paper aspires to identify the most influential factors that affect the sustainability of a biodiesel plant and describe interactions among them. The study focuses on identifying 36 factors based on an extensive literature review, questionnaire, experts' opinion and website in the context of developing economies. These factors include social, environmental and economic aspects. A framework based on fuzzy-interpretive structural modelling (F-ISM) and fuzzy-decision-making trial and evaluation laboratory (F-DEMATEL) is applied to investigate the identified factors. The F-ISM approach allows a better understanding of the contextual interactions between the factors and classify them based on their driving and dependent powers. The fuzzy-DEMATEL technique facilitates in identifying the influential and influenced factors and categorizes them into cause-and-effect groups. The findings of the study suggest that 'Legal and regulatory compliances', 'Political constraints', 'International relations', 'Health and education' and 'Public safety and security' are the five most influential factors that are needed to be addressed for the sustainability of biodiesel plant. The paper also presents a few strategies, which can be applied as a guiding step by the decision-makers to formulate policies for the effective implementation of sustainable growth of the biodiesel plant